“O maior arraial da Amazônia” : um olhar geográfico sobre a dinâmica dos Festejos Juninos em Boa Vista/RR - Silva, Glauciene Dutra (2017)
This research titled "The biggest camp in the northern region": A geographical look on the dynamics of the Juninho Celebrations in Boa Vista / RR, aims to understand how to design the dynamics of state fairs in Roraima capital, which set as "intangible cultural heritage", relating to the political, economic, and sociocultural. understand this set of state fairs with social, methodologies were needed on site, bibliographic research on the themes: popular culture, cultural heritage, identity, play space, territoriality, concepts that were very important to understand the dynamics of this junina with the social set. With the phenomenological method, since this method is more suitable to understand the complexities of the objects and subjects of study, and the June Festival and the gang groups. The methodology was supported by interviews, observations and questionnaire with gang groups involved in the research. The groups were chosen by three criteria: the group that won the contest of "Boa Vista Junina" 2015 year that begins this research; the pioneer of the camp and the group has a mass culture. The research subjects, according to the mentioned criteria, here are represented by groups: Grit blast, the gang Ze Monteirão, and Eita Junino group. The groups were followed during their months of rehearsals and during his performances in "Boa Vista Junina". What obtained as a result that popular culture when it passes be considered as "cultural heritage" that is not to say that it can not change, unlike culture is renewed in accordance with social changes, as is somehow result of their behavior.